Understanding the evolution and function of the mycobacterial Type VII ESX secretion systems (T7SSs) and their substrates - Newton-Foot, Mae (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.